Analysis of the contact conditions between chip and tool using nanostructured coated cutting tools. (8th January 2008) - Jackson, Mark J.; Whitfield, Michael D.; Morrell, Jonathan S.
The stages of contact between a metal chip of AISI 1018 steel and a coated cutting tool creates significant opportunities for manufacturers of machined products to understand how dry machining and minimum quantity lubrication affects the economics of manufacturing. The present work not only compares various computational approaches to the solution of shear plane and tool face temperatures during dry machining with nanostructured coated milling tools, but also explains why there is a large discrepancy when calculating temperature generated during machining when using Loewen and Shaw's method for calculating shear plane and tool face temperatures.